Deskripsi Pelayanan Konseling dalam Etis Kristiani Bagi Pendidikan Karakter Kristen - Lahingide, Yenni Olivia; Sumiyati, Sumiyati (Jurnal Lentera Nusantara, 2021)
Counseling is always related to a solution that will be sought to solve every problem, the solution sought is of course based on the truth of God's word, restoring a fragile condition means that the counseling process can restore a fragile and fragile condition that is replaced with toughness, patience and fortitude, change attitudes and behavior. Using descriptive qualitative methods with the aim of the importance of counseling services in Christian ethics, counseling services in Christian ethics for Christian education and character can be concluded that counseling services must be maintained as indicated by the statement item "Counselors teach about God." Counseling services need to improve understanding of the inmates' character as indicated by the statement item "Counselors help me to correct bad behavior and attitudes." Furthermore, the character in Christian education must be maintained based on the Word of God.” Counseling services also need to improve the character of Christian education which is shown in the value of being responsible for each task. To the Pastor or all God's servants who perform counseling services in church and educational institutions so that they always provide an understanding of the importance of each person having a good character. The last is for the reader to understand and understand correctly about counseling services, and participate in the counseling services that are carried outAbstrakKonseling selalu berhubungan dengan adanya solusi yang akan dicari untuk menyelesaikan setiap permasalahan, solusi yang dicari tentunya berpatokan dengan kebenaran firman Tuhan, memulihkan kondisi yang rapuh artinya proses konseling dapat memulihkan kondisi yang rapuh dan kerapuhan itu berganti dengan ketegaran, kesabaran dan ketabahan, perubahan sikap dan perilaku. Mengunakan metode kualitatif deskritif dengan tujuan pentingnya pelayanan konseling dalam etis Kristiani maka Pelayanan konseling dalam Etis Kristiani bagi pendidikan Kristen dan karakter dapat disimpulkan bahwa Pelayanan konseling supaya tetap dipertahankan yang ditunjukkan dengan item pernyataan “Konselor mengajarkan tentang Allah.” Pelayanan konseling perlu meningkatkan pemahaman karakter warga binaan yang ditunjukkan oleh item pernyataan “Konselor menolong saya untuk memperbaiki tingkah laku dan sikap yang buruk.” Selanjutnya karakter dalam pendidikan Kristen supaya tetap dipertahankan dengan berdasarkan Firman Allah.” Pelayanan konseling juga perlu meningkatkan karakter pendidikan Kristen  yang ditunjukkan oleh dalam nilai bertanggung jawab atas setiap tugas. Terhadap kepada Gembala Sidang atau semua hamba-hamba Tuhan yang melakukan pelayanan konseling di lembaga gereja maupun pendidikan agar selalu memberikan pemahaman tentang pentingnya setiap orang memiliki karakter yang baik. Yang terakhir kepada pembaca supaya mengerti dan memahami dengan benar tentang pelayanan konseling, serta ikut dalam pelayanan konseling yang   dilakukan.